THE EFFECT OF THE BILINGUAL STORY BOOK ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Hj. Noviati Hj. Noviati; Evi Rosmiyati (Esteem Journal of English Education Study Programme, 2022)
The main of this study  “was there any significant effect on the Second semester students’ reading comprehension achievement after being taught by using Bilingual Story Book and those who are not? The population of  this study was the second semester PGSD Study Program FKIP University PGRI of Palembang in academic year 2019/2020. The total number of the population was 120 students, The sample consisted of 36 students of 2O and 36 students of 2Q. The method of the research was the experimental method and the data were collected through written test in multiple choice form. The test was administrated twice as the pre-test and post-test. The result were analyzed by using t-test. The students’ average score of pretest in control class of 2O were 59.20 and 6.12. While the students’ average score of post test in experimental class of 2Q were 6.52 and 7.13. And By using those result, it was found that the result of this research based on her students’ average score of post test in experimental and control class was 4.779 that is higher than its the critical value. The null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.